2023
DOI: 10.3389/fcimb.2023.1228376
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A spinal infection with bilateral psoas abscesses was treated with NPWT to enhance the local infection by increasing the infiltration of neutrophil cells and draining the pus

Abstract: Treatment of spinal brucellosis with bilateral psoas abscess is a challenging clinical endeavor. We retrospectively evaluated a case of lumbar infection and bilateral psoas abscess, and was effectively managed through a unilateral extreme lateral approach with the aid of NPWT for bilateral drainage. We hypothesize that NPWT can influence the Piezo1 receptor of neutrophils and further influence the interaction between neutrophils and endothelial cells to promote the clearance of infected lesions, and this pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In addition, the gradual negative pressure effect on the wound edges helps to improve vascularization of the tissue, thus facilitating the healing process. After reviewing the literature and observing clinical cases, we have found that the negative pressure effect of VSD can generate mechanical force that helps recruit immune cells around the incision edge [ 31 ]. This leads to a significant increase in the number and density of neutrophils, which enhances local immune function.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the gradual negative pressure effect on the wound edges helps to improve vascularization of the tissue, thus facilitating the healing process. After reviewing the literature and observing clinical cases, we have found that the negative pressure effect of VSD can generate mechanical force that helps recruit immune cells around the incision edge [ 31 ]. This leads to a significant increase in the number and density of neutrophils, which enhances local immune function.…”
Section: Discussionmentioning
confidence: 99%